Wellness aqua programs through adapted physical activity and sports for children with special needs (Research Announcements "Heritage BG", 2025)
Motor activity practiced by children with special needs can be defined as any activity that adapts to the capabilities of each child, with the main emphasis on physical development and psycho-emotional state. Adapted exercises performed in an aquatic environment as part of wellness practices for children with various disabilities is highly recommended, as they can be modified and adapted for each age at different stages of motor development. Aqua practices are important as they improve the general condition of the child’s body, facilitate daily activities and social interaction and enable independence and safety in the aquatic environment. References:Aleksandrova 2019: Aleksandrova, Velichka. Zdravna prevencia pri deca sas sindrom na Asperger chrez dvigatelna aktivnost vav vodna sreda. Mejdunarodno nauchno spisanie ‘Smart inovacii, rekreativna industria, wellness cultura, nishov turizam’, elektronno izdanie, br. 2, 43-57.Aleksandrova 2021: Aleksandrova, Velichka. Adaptirano pluvane za deca s uvrejdania. Monografia.Aleksandrova, Djobova, Kirilova, Hristov 2017: Aleksandrova, Velichka, Stefka Djobova, Ivelina Kirilova, Oleg Hristov. Adaptirana fizicheska aktivnost i sport. Elektronno pomagalo, NSA, Sofia.Bahchevanski 2019 : Bahchevanski, Stoian. Zanimaniata s vetrohodstvo kato sredstvo za integracia pri deca s uvrejdania. Nauchno-prilojna konferencia ‘Fizicheska aktivnost i zdrave’, Sbornik s dokladi., 77-82, Sofia.Bulgakova 2008: Bulgakova, Natasha. Ozdravitelnoe, lechebnoe i adaptivnoe plavanie. Uchebnoe posobie dla studentov vishee uchebnovo zavedenii. Akademia, Moskva.Carova 2013: Carova, Rosica. Basketbol v invalidni kolichki. Monografia. Sofia, Boulid – ins.Dimitrova et al. 2021: Dimitrova, Bistra, Nikolay Izov, Velichka Alexandrova, Rumen Iosifov, Darinka Ignatova, Dimitar Trendafilov, Vasil Petrov, Gergana Vasileva. Smart kognitiven instrumentarium. Vŭnshna otsenka na profesionalni kompetentsii za kadri v Nishov turizŭm. NSA Press. Sofia.Djobova 2019: Djobova, Stefka. Fizicheska aktivnost I sportive v otkrita vodna sreda pri hora s mentalni uvrejdania. Sbornik s dokladi. Naushno-prilojna konferencia ‘Fizisheska aktivnost i zdrave’, 89-97.Ivkov 2013: Ivkov, Bojidar. Analiz na potrebnostite na horata s uvrejdania ot socialno vkluchvane chrez zaetost. Proekt ‘Ravni vazmojnosti, realizacia, razvitie’, № BG 051Р0001-5.1.05-0008-С0001. Sofia.Kirilova, Djobova, Andondv 2018: Kirilova, Ivelina, Stefka Djobova, Stoian Andonov. Zanimania pri deca sas sindrom na Daun vav vodna sreda – specifichni riskove. Sport i sigurnost, 47-51, Sofia.Nesheva 2019: Nesheva, Irina. Adaptirana dvigatelna metodika sas sredstvata na gimnastika pri hora s uvreden sluh. Nauchno spisanie za Smart inovacii v rekreativnata (Wellness) industria i Nishov turizam, 37-42, Sofia.Nikolova 2011: Nikolova, Maia. Ozdravitelno-reshabilitacionno pluvane. Monografia, NSA PRES, Sofia.Popov, Izov, Andonov 2018: Popov, Ivan, Nikolai Izov, Stoian Andonov. Pluvane. Uchebnik za student ot NSA ‘Vasil Levski’. Sofia.Tumanova 2019: Tumanova, Boriana. Pluvaneto – Sistema na zdravosloven nachin na jivot. Rekreativna & Wellnessindustria I nishov turizam, Elektronno izdanie, br. 1, 11-14, Sofia.Donev et al. 2019: Donev Jordan, Stoyan Andonov, Stefka Djobova, Jordan Donev, Oleg Hristov, Ivelina Kirilova, Stoyan Bahchevanski, Rumen Iossifov, Velichka Aleksandrova, Bogomil Angelov, Natalia Stoyanova. Comparative Study of Measuring Physical Activity Among Sport Students. International Scientific Congress ‘Applied sports sciences. Balkan Scientific Congress of Physical Education, Sports and Health”, 15 – 16 November 2019, Sofia, Bulgaria. Proceedings book, 369-374.Ignatova, Iliev 2020: Ignatova, Darinka, Alexandar Iliev. Motor Qualities and Their Influence on Children’s Development. International Scientific Journal: Smart Innovations in Recreation, Wellness Industry and Niche Tourism, No 2 (1-2), 16-20.Ivanova 2019: Ivanova, Vessela. Influence of Gymnastic Exercises in the Water Environment. International Scientific Journal: Smart Innovations in Recreational, Wellness Industry and Niche Tourism. No 1 (1), 53-56.Nesheva 2019: Nesheva, Irina. Study of Results Between Initial and Final Specific Tests in Women with Normal Pregnancy. Trakia Journal of Sciences, No 17 (2), 135-142.Nesheva 2020: Nesheva, Irina. Information system for inclusion of women with normal pregnancy in gymnastics program. “Smart Innovations on the Recreative & Wellness Industries and Niche tourism”, Sofia, No 2 (1), 33-39. ISSN: 2603-4921.Internet sources:http://www. halliwick.orghttp://www.jahara.com
Keywords: children; special needs; wellness aqua programs